1994
DOI: 10.1002/1097-0142(19940501)73:9<2386::aid-cncr2820730923>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Perfusion and metabolism in predicting the survival of patients with cerebral gliomas

Abstract: Background. Noninvasive measurements of cerebral circulation and metabolism may be useful for diagnosis in patients with brain tumors. The authors tested the prognostic significance of circulatory and metabolic values or ratios determined by positron emission tomography (PET) in patients with gliomas. Methods. The subjects were 23 patients, who underwent a complete PET study of cerebral circulation and metabolism with long‐term follow‐up of at least 57 months. Regional cerebral blood flow (rCBF), blood volume … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(31 citation statements)
references
References 26 publications
3
28
0
Order By: Relevance
“…[ 18 F]FDG uptake in gliomas is related to the degree of histological malignancy, and is a predictor of survival time. 10) In the present case, high uptake of [ 18 F]FDG indicated a malignant lesion at the first operation. However, the interval from initial symptoms to death was about 7 years, and the remaining eye kept useful visual acuity despite hemianopsia, suggesting that the tumor had undergone malignant transformation.…”
Section: Discussionsupporting
confidence: 47%
“…[ 18 F]FDG uptake in gliomas is related to the degree of histological malignancy, and is a predictor of survival time. 10) In the present case, high uptake of [ 18 F]FDG indicated a malignant lesion at the first operation. However, the interval from initial symptoms to death was about 7 years, and the remaining eye kept useful visual acuity despite hemianopsia, suggesting that the tumor had undergone malignant transformation.…”
Section: Discussionsupporting
confidence: 47%
“…In a recent study, Helmlinger et al (1997) measured PO 2 using a phosphorescence quenching microscopy technique in human tumour xenografts, and reported that hypoxic (≤ 5 mmHg) and near anoxic values (0-0.5 mmHg) were reached 70-80 and ≥ 150 µm away from tumour vessels respectively. However, a few histological studies on malignant gliomas have failed to obtain a certain tendency of tumour vascular density (Yoshii and Sugiyama, 1988;Stewart et al, 1991;Wesseling et al, 1994), although blood flow is lower in malignant gliomas than in normal white matter (Ito et al, 1982;Tyler et al, 1987;Mineura et al, 1994). These conflicting observations support the hypothesis that tumour tissue perfusion is incomplete due to transient (acute hypoxia) or partial occlusion of vessels (Chaplin et al, 1986).…”
Section: Tumour Hypoxiamentioning
confidence: 98%
“…Because oxygen consumption is lower in malignant gliomas than in the normal brain (Ito et al, 1982;Tyler et al, 1987;Mineura et al, 1994), tumour hypoxia is induced by low tumour blood flow. Radioresistance caused by hypoxia is thought to develop by two major mechanisms: diffusion-limited or chronic hypoxia, due to reduced oxygen diffusion to regions distant from the tumour vessels (Thomlinson and Gray, 1955), and acute hypoxia caused by transient occlusion of vessels (Chaplin et al, 1986).…”
Section: Tumour Hypoxiamentioning
confidence: 99%
See 1 more Smart Citation
“…The glucose metabolic rate of such tumours has been shown to be an accurate predictor of histological tumour grade as well as of patient survival, information that often effects management [8][9][10]. Although it was first demonstrated in the de novo evaluation of such tumours, there is some evidence that this relationship might also apply in the setting of prior therapeutic intervention [11,12].…”
mentioning
confidence: 99%